Влияние лазерного излучения на структуру корневого дентина по данным изучения на сканирующем электронном микроскопе (LLC "Endo Press", 2020)
Studying of influence laser radiation diode laser with length of a wave 1040 nanometers on structure root dentin is spent at endodontic preparation of a teeth for sealing, and also an estimation of degree regional fit filling material to walls of the root channel by means of a method of scanning electronic microscopy. Researches spent on 48 samples the live teeth removed under medical indications. Results of the carried out research have shown high efficiency of processing root channels with the help diode laser, influencing density fit a root seal.